P215 Filgotinib, a janus kinase 1 selective inhibitor, modulates disease-associated cytokines in patients with active RA. (20th April 2020) - Taylor, Peter C; Elboudwarej, Emon; Li, Wanying; Hawtin, Rachael E; Liu, Jinfeng; Mirza, Amer M
Abstract: Background: Filgotinib (FIL), an oral JAK1-selective inhibitor, was safe and effective in FINCH2, a randomised, double-blind, placebo (PBO)-controlled, phase 3 study in patients with active rheumatoid arthritis (RA) who had an inadequate response to methotrexate (MTX) and ≥1 biologic disease-modifying antirheumatic drug. A longitudinal study of cytokines from patients in FINCH2 was conducted to identify RA-associated biomarkers related to bone biology, immune cell migration, and inflammation that are altered by FIL therapy; and FIL-associated biomarkers that correlate with clinical response (DAS28CRP, swollen and tender joint counts, pain, and fatigue). Methods: Plasma, serum and urine samples from RA patients (n = 449) receiving FIL (100mg, 200mg) or PBO once daily plus MTX were analysed at baseline (BL) and week 12 (W12) for 42 disease-relevant cytokines using validated, commercially available single- or multiplex assays. PBO corrected on-treatment changes in cytokine levels from BL to W12 were compared between treatment arms (Wilcoxon rank sum). Spearman rank correlation was used to compare changes in cytokine level from BL to W12 and clinical response. P-values <0.05 were considered significant. Results: At W12, 18 of 42 cytokines significantly decreased with FIL 100mg treatment relative to PBO; FIL 200mg decreased these cytokines to a similar or greater degree. An additional 6 cytokines were significantly decreased by FIL 200mg. Conversely, 2 cytokines increased relative to PBO with FIL 100mg, and 6 cytokines increased with FIL 200mg (sIL-6R, IL10, GMCSF, IL2, leptin, and IL17A). Biomarkers most significantly modulated by FIL 200mg (p < 0.0001) included markers related to bone biology (MMP1 [-22.8%], MMP3 [-24.7%], CTX1 [-27.4% ], and NTX [-16.4%]), immune cell migration (VCAM1 [-20.0%], ICAM1 [-14.2%], CXCL13 [-45.0%], and CXCL10 [-32.3%]), and inflammation (TNFRI[-20.7%], CRP [-77.4%], SAA [-61.8%], and resistin [-20.2%]). Hierarchical clustering of BL biomarker levels revealed distinct groups of cytokines that were strongly correlated with each other. Among them, SAA, IL6 and CXCL10, were significantly positively correlated with each other (rho>0.6) and with RA disease activity (DAS28CRP) at BL (rho>0.3). Biomarkers, including CRP (IL6, SAA), PainVAS (CRP, SAA), and SJC28 (CRP, IL6, CXCL10), were also significantly correlated with individual components of DAS28CRP. Several biomarkers associated with RA disease activity at BL were decreased with FIL at W12 relative to PBO (FIL 100mg: CRP [-48.7%], SAA [-36.9%], and IL6 [-2.6%] and FIL 200mg: CRP [-77.4%], SAA [-61.8%], IL6 [-13.6%], CXCL10 [-32.3%]), suggesting FIL impacts these disease activities at a molecular level. Conclusion: Twelve weeks of FIL treatment significantly reduced 24 disease-relevant cytokines in patients with active RA. Effects were dose-dependent and suggest a shift toward restored immune homeostasis. Findings are consistent with the clinical efficacy of FIL in FINCH2. Disclosures: P.C. Taylor: Consultancies; Consultant for AbbVie, BMS, Jansses, Pfizer, Roche, Lilly, Sanofi, MSD, Novartis, Celgene and Gilead. E. Elboudwarej: Corporate appointments; Employee of Gilead Sciences, Inc. Shareholder/stock ownership; Shareholder of Gilead Sciences, Inc. W. Li: Corporate appointments; Employee of Gilead Sciences, Inc. Shareholder/stock ownership; Shareholder of Gilead Sciences, Inc. R.E. Hawtin: Corporate appointments; Employee of Gilead Sciences, Inc. Shareholder/stock ownership; Shareholder of Gilead Sciences, Inc. J. Liu: Corporate appointments; Employee of Gilead Sciences, Inc. Shareholder/stock ownership; Shareholder of Gilead Sciences, Inc. A.M. Mirza: Corporate appointments; Employee of Gilead Sciences, Inc. Shareholder/stock ownership; Shareholder of Gilead Sciences, Inc.